2010
DOI: 10.1111/j.1365-2354.2008.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of pancreas with liver metastasis combined with gastrointestinal stromal tumour of the stomach: is there a good prognosis with the complete resection?

Abstract: We report a carcinosarcoma of the pancreas with liver metastasis combined with gastrointestinal stromal tumour (GIST) of the stomach in a 72-year-old woman who presented with right upper quadrant pain, nausea and vomiting. A radical resection including pancreaticoduodenectomy, left hepatic lobe resection and local resection of the gastric mass was performed. The tumour in the head of pancreas was found to be grossly yellow-white, and it infiltrated the common bile duct and duodenum; the mass of the liver metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
0
17
1
Order By: Relevance
“…The patients survived an average of only 6 months after surgery. Shen et al [7] reported an old woman with carcinosarcoma of pancreas with liver metastasis combined with gastrointestinal stromal tumor of the stomach. Though the patient received radical resection, she died 2 months postoperatively because of recurrence.…”
Section: Discussionmentioning
confidence: 98%
“…The patients survived an average of only 6 months after surgery. Shen et al [7] reported an old woman with carcinosarcoma of pancreas with liver metastasis combined with gastrointestinal stromal tumor of the stomach. Though the patient received radical resection, she died 2 months postoperatively because of recurrence.…”
Section: Discussionmentioning
confidence: 98%
“…Shen et al (9) reported a carcinosarcoma of the pancreas with liver metastasis combined with a gastrointestinal stromal tumor of the stomach in a 72-year-old female. A radical resection, including a pancreaticoduodenectomy, left hepatic lobe resection and local resection, of the gastric mass was performed, however, the patient succumbed to multiple organ failure at 2 months post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…One report mentioned sarcoma. Data were not large enough for statistical analysis (2,4,(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%